Cascading hazards and hazard mitigation plans: Preventing cascading events in the United States. Issue 1 (18th May 2021) - Chen, Joanne; Greenberg, Michael
Abstract: The concentration of people and commerce in densely packed megacities has created interconnections between engineered and human‐service systems that are susceptible to a single potentially hazardous event triggering others. We identify the interdependencies between engineered and human‐service systems as well as the progression of hazardous cascading effects in the US context. The three purposes of this paper are (1) to determine how much attention is paid to cascading events in state and local hazard mitigation plans in the United States; (2) evaluate findings in the context of other environmental health programs in these places, noting that the paper is based on reviews of recent state and selected local hazard mitigation plans; and (3) offer suggestions for jump‐starting focus on cascading events in hazard mitigation plans. Cascading events have not been a focus of US hazard mitigation plans, but we find a trend toward more attention, especially in states and cities that have a history of innovative environmental health and protection programs. Given a new administration in Washington, DC,  we urge legislators and risk managers to be more aggressive about the challenge of cascading events. 摘要: 人口密集的特大都市中人和商业的集中化已使工程系统和人类服务系统之间产生关联，这种关联易受能触发其他事件的单一潜在危害事件的影响。我们识别了美国工程系统和人类服务系统之间的相互依赖性，以及灾害级联效应（cascading effects）的发展。本文的三个目的分别是（1）确定美国各州和地方的灾害缓解计划中级联事件（cascading events）所受到的关注度；（2）在上述地点的其他环境卫生计划背景下评价研究发现，审视了近年来各州和部分地方的灾害缓解计划；（3）为加大研究灾害缓解计划中的级联事件提供建议。级联事件目前还不是美国灾害缓解计划的焦点，但我们发现存在关注度上升的趋势，尤其是在曾经有过创新性环境卫生和保护计划的那些州和城市。鉴于华盛顿特区迎来了新政府，我们敦促立法者和风险管理者更加关注级联事件的挑战。 Resumen: La concentración de personas y comercio en megaciudades densamente pobladas ha creado interconexiones entre los sistemas de ingeniería y de servicios humanos que son susceptibles a un solo evento potencialmente peligroso que desencadena otros. Identificamos las interdependencias entre los sistemas de ingeniería y de servicios humanos, así como la progresión de los efectos peligrosos en cascada en el contexto de los EE. UU. Los tres propósitos de este documento son (1) determinar cuánta atención se presta a los eventos en cascada en los planes estatales y locales de mitigación de peligros en los EE. UU.; (2) evaluar los hallazgos en el contexto de otros programas de salud ambiental en estos lugares, señalando que el documento se basa en revisiones de planes de mitigación de peligros locales seleccionados y estatales recientes; y (3) ofrecer sugerencias para comenzar a enfocarse en eventos en cascada en los planes de mitigación de peligros. Los eventos en cascada no han sido un foco de los planes de mitigación de peligros de EE. UU., Pero encontramos una tendencia hacia una mayor atención, especialmente en los estados y ciudades que tienen un historial de programas innovadores de protección y salud ambiental. Dada una nueva administración en Washington, D.C., instamos a los legisladores y administradores de riesgos a ser más agresivos ante el desafío de los eventos en cascada.